Discussion on Disaster Remote Sensing Application Service Based on Ground Information Port - Qiao HU; Zuoya ZHENG; Gang LIU; Linyao QIU; Yanfeng WU (天地一体化信息网络)
Aim at the problems of large volume and low degree of sharing of remote sensing data, high complexity of algorithm model and single function of disaster response application system, the main functions and technical framework of GIP, as well as the advantages and potential of GIP in platform, algorithm and application system was introduced.It provided a reference for further mining the research of new intelligent processing algorithm and processing mode for multi-source, high-dimensional, heterogeneous and complex associated earth observation data in other application fi elds with GIP, so as to promote the service ability and form a new information service mode and industrial chain of the GIP.